Macro-surface Modification through Exploitation of Rivets and Dimples –Numerical and Experimental - Mohd Danial, Bin Ibrahim; Mohd Shahril, Bin Osman; Miyanaga, Norifumi; Amir Azam, Khan (2013)
Research related to rivets and dimples has been conducted as early as the 1930s. The irregularities of surfaces have believed to be a factor to fuel consumption increase of airplanes. NASA reported that it is vital to eliminate the surface irregularities or other protuberances from the surface that is exposed to the airflow [1]. This is believed to due to the extreme increase of the drag coefficient.